Magnetically modified Posidonia oceanica biomass as an adsorbent for organic dyes removal - I. SAFARIK (Mediterranean Marine Science, 2016)
Magnetically modified Posidonia oceanica sea grass dead biomass was employed as an adsorbent of organic dyes. The adsorption of seven water-soluble organic dyes was characterized using Langmuir adsorption model. The highest calculated maximum adsorption capacity was found for Bismarck brown Y (233.5 mg g-1), while the lowest capacity value was obtained for safranin O (88.1 mg g-1). The adsorption processes followed the pseudo-second-order kinetic model and the thermodynamic studies indicated spontaneous and endothermic adsorption.